Etnomatematika Bentuk Bangun Geometri Pola Seni Ukiran Kudus Pada Rumah Adat Jawa - Ita Erlina Ariyanti; Putri Nur Malasari (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
Ethnomatematics is the application of mathematical concepts in the culture that exists in society. This research was conducted at the Joglo Kudus Carving Art Industry Center located in Garung Lor Village, Kaliwungu District, Kudus Regency, Central Java. The purpose of this research is to explore the concept of geometry in the pattern of the Kudus carving art which is applied to the manufacture of Javanese Traditional Houses. The type of research used is qualitative research using an ethnographic approach. The data collection method was carried out by interviewing 3 carving workers, observation and documentation. The object of this study is the carving motifs that exist in several parts of the Javanese traditional house, including ceilings, tumpang, sunduk, katek, blandar, and umpak. The results obtained from the research show that there is a geometric concept of the art pattern of Kudus carvings found in Javanese traditional houses in the form of straight lines, curved lines, sharp angles, squares, rectangles, trapezoids, parallelograms, rhombuses, circles, semicircles, octagons, pyramids. rectangles, blocks and cubes. This research is expected to make it earsier for students to understand the implementation of mathematics in the surrounding culture.